2017
DOI: 10.5152/iao.2017.3764
|View full text |Cite
|
Sign up to set email alerts
|

Eustachian Tube Obliteration and its Effect on Rhinoliquorrhea in Translabyrinthine Vestibular Schwannoma Excision

Abstract: OBJECTIVE:Rhinoliquorrhea is defined as a cerebrospinal fluid leakage from the nose. Our objective in this study is to determine the reduction of rhinoliquorrhea rates by Eustachian tube (ET) obliteration in the context of a translabyrinthine approach performed following vestibular schwannoma (VS) excision. MATERIALS and METHODS:This is a prospective study achieved in a tertiary-care center where the chart review revealed 94 VS operated by the translabyrinthine approach between 2009 and 2015. There were 40 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Most studies were retrospective (39/43), and all were case series. Four studies had at least one arm which was prospective [15][16][17][18] . Twelve out of 43 studies compared different techniques or materials.…”
Section: Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies were retrospective (39/43), and all were case series. Four studies had at least one arm which was prospective [15][16][17][18] . Twelve out of 43 studies compared different techniques or materials.…”
Section: Overviewmentioning
confidence: 99%
“…Several studies reported an onlay technique to seal the dura, employing autologous grafts, xenografts and synthetic dural substitutes. 17,21,22,25,42,[47][48][49][50] Autologous onlays consisted of fascia grafts, harvested either from the abdomen or thigh. 17,22,25,42,48,51 Variations in the autologous onlay technique centred around the size of the graft used, ranging from slightly larger than the dural defect to a 'peri cranial graft basket' 47 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations